Brucella Blastongenesis of Rabbits Lymphocytes Sensitized with Outer Membrane Proteins. Lipopolyccharide and Lipid-A. Associated Protein Extracted from melitensis. - N. A. Mohymen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
The study conformed rabbit lymphocytes on Blastogenesis assay was sensitized with  outer membrane proteins (OMP), lipopoly saccharine LPS) and Lipid. A. Associated protein (LPA) extracted from brucella (filed strain). Results showed that there was an increase in melitensis the mitotic index (M.I) induced by LPA (19,48) and OMP (11.7) with while LPS induced lower value of MI (7.61).